CLUTCH OPERATING DEVICE WITH FRICTION LINING WEAR COMPENSATION ANALYSIS OF PROPERTIES AND UTILIZATION EFFICIENCY - Рябуха, Ю. А.; Михалевич, Н. Г.; Воронова, Е. М.; Ярита, А. А.; Клименко, В. И.; Рябуха, Ю. О.; Михалевич, М. Г.; Воронова, Е. М.; Ярита, О. О.; Клименко, В. І.; Riabukha, Iu. A.; Mikhalevich, N. G.; et al. (My University, 2017)
Design of the clutch operating device with reduced dimensions is examined. Its properties have been analysed and effect of using of the design in operation is shown
МЕХАНІЗМ КЕРУВАННЯ ЗЧЕПЛЕННЯМ З КОМПЕНСАЦІЄЮ ЗНОСУ ФРИКЦІЙНИХ НАКЛАДОК. АНАЛІЗ ВЛАСТИВОСТЕЙ І ЕФЕКТИВНОСТІ ВИКОРИСТАННЯ
МЕХАНИЗМ УПРАВЛЕНИЯ СЦЕПЛЕНИЕМ С КОМПЕНСАЦИЕЙ ИЗНОСА ФРИКЦИОННЫХ НАКЛАДОК. АНАЛИЗ СВОЙСТВ И ЭФФЕКТИВНОСТИ ИСПОЛЬЗОВАНИЯ
Keywords: ПГУ; механизм компенсации износа фрикционных накладок; экономия топлива; уменьшение потребления сжатого воздуха; ПГУ; механізм компенсації зносу фрикційних накладок; економія палива; зменшення споживання стисненого повітря; PHB; compensation mechanism for friction linings wear; fuel economy; reduction of compressed air consumption; 681.583.35